Notas sobre la estructura de la propiedad en la minería de carbón leonesa - Redondo Vega, José María (Estudios humanísticos. Geografía, historia y arte, 1988)
The structure of the property in Leon's coal mining is based on the existence of smalle mines, a fact that makes the mining space a very fragmented one. This charasteristic, which is a historial fact in the beginning of the coal mining, has developed slowly theroughout the last decades towards a concentration of the properties, with a small number of owners. The concentration process is very impotant in the hard coal mines, and much less visible in the anthracite ones, where we still find an important number of reduced extension mines belonging to small owners.